Parole in South Africa : is it a right or a privilege? : the theory and practice of parole in South African Correctional centres with specific focus on the nature of parole under the Correctional Service Act 8 of 1959 (repealed) and the current Correctional Service Act 111 of 1998 - Moses, Jacobus Johannes (Institute of Criminology, 2015)
Includes abstract.